Diffusion and interface controlled reactions in alpha-(Cu-Al-Ag) alloys - Adorno, A. T.; Silva, R. A. G.; Magdalena, A. G. (Elsevier B.V., 2007)
The isothermal kinetics of Ag precipitation was studied in Cu-Al-Ag alloys with concentrations ranging from 2 to 8 wt.%Al and 2 to 12 wt.%Ag, using scanning electron microscopy (SEM), X-ray energy dispersive spectroscopy (EDX) and microhardness measurements. The results indicated a change in the precipitates growing mechanism from diffusion to interface controlled process, probably due to a change in the nature of the interface with the Ag and Al enrichment of the precipitates. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: metals and alloys; precipitation; diffusion; kinetics